Kombinasi Akupressure Dengan Yoga (Acuyoga) Terhadap Nyeri Punggung Pada Ibu Hamil Trimester III : Studi Literatur - Syafitasari , Juanda; Putri , Poppy Siska; Afriannisyah , Entan (Jurnal Kebidanan Manna, 2023)
Pregnancy experiences many physiological and psychological adaptations, being vulnerable to all kinds of stress resulting in changes in physiology and metabolic function. Improper body posture will force additional stretching and fatigue in the body, especially the spine, so back pain will usually increase in intensity as pregnancy increases. Nearly 50% of lower back pain is experienced by pregnant women. As many as 43.9% of pregnant women experience lower back pain in the second trimester. Acuyoga uses a combination of yoga movements and pressure on organ meridian points to increase vital energy (qi). And combined knowledge of acupuncture/acupressure and yoga which regulates the flow of vital energy in the meridians of the organs. Vital energy is called prana (in yoga) or qi (in acupuncture) and ki (in Japanese medicine). The aim is to analyze acupressure and yoga methods in reducing back pain for pregnant women in the third trimester so that they can choose to use the most effective method to overcome discomfort during pregnancy. The research method used is a systematic literature review. Research articles were reviewed using national and international electronic journal search strategies, namely Google Scholar and Science Direct using keywords. Electronic journals obtained from 15 of 395 journals about acupressure for reducing back pain in pregnant women, publications ranging from 2009-2019, using Indonesian and English are presented in this review. The results of this study show that non-pharmacological holistic therapies such as acupressure and yoga can be applied to reduce back pain in third trimester pregnant women.